Beyond the paranoid style - fascism, radical right and the myth of conspiracy: fifth Convention of the International Association for Comparative Fascist Studies (COMFAS) - Jackson, Paul (Fascism, 2022)
Following two years of online events, from the 14 to 16 September 2022 the fifth annual Convention of the International Association for Comparative Fascist Studies (COMFAS) took place in Florence. The title of the conference ‘Beyond the Paranoid Style: Fascism, Radical Right and the Myth of Conspiracy’ presented a framework for a wide variety of reflections that were both historically grounded and timely. After all, in the wake of the Covid-19 pandemic, many scholars have had new experiences of the impact of conspiracy theory thinking.